FITOREMEDIASI TANAH TERCEMAR LOGAM BERAT MERKURI (Hg) MENGGUNAKAN TUMBUHAN KERSEN (Muntingia Calabua L) DENGAN SISTEM REAKTOR - Silvia M Borolla; A Mariwy; J Manuhutu (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
Heavy metal pollution is a serious problem to environment in this time. Mercury is a dangerous wastes that make desecrate environment. So the restoration have to do to make a contaminated soil can reuse safety through fitoremediation process using Kersen. This study to analyze the reductions of heavy metal (Hg) in soil after fitoremediation process. The result of this study was showing that connections between degree reductions of heavy metal (Hg) in soil and adsorptions of Mercury (Hg) in Kersen that is concentration mercury in soil more high reductions than in the soil will following of higher Mercury concentrations in Kersen, in this study showing that adsorptions of Kersen in week – 1 after mercury treatment on a sample is in soil 6,80 ppm, root 1,14 ppm, leaf 0,86 ppm in week - 2 for soil sample is 7,31 ppm, root 3,73 ppm, leaf 4,64 ppm and for the last week in soil is 7,98 ppm, root 0,07ppm and leaf is 0,78 ppm. From that result showing Kersen (Muntingia Calabura L) is a accumulator plant and this plant can using for hyperaccumulation because the value of BCF and TF in day 14 or week – 2 is > 1.